ANALYSIS OF THE ISLAMIC EDUCATION LEARNING MODEL WITH SPECIAL NEEDS AT PAS BAITUL QUR’AN NGABAR PONOROGO INCLUSIVE KINDERGARTEN - Syarifah Syarifah; Agum Rijal Ainalyaqin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the instructional planning design, implementation models, and assessment of Islamic Religious Education (PAI) learning at PAS Baitul Qur’an Inclusive Kindergarten in Ponorogo. A qualitative descriptive approach was employed, involving the principal, PAI teachers, and inclusion facilitators as research participants. Data were collected through semi-structured interviews, participatory observation, and document analysis, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that PAI instructional planning is developed adaptively by considering the individual needs of children with special needs and principles of early childhood development. Learning implementation is carried out through four main models: individual, transition, group, and center-based learning, which facilitate gradual, flexible, and inclusive learning experiences. Assessment is conducted authentically and continuously using observation, performance, and portfolio techniques, serving as a tool for monitoring children’s religious and social development rather than merely evaluating learning outcomes. This study concludes that PAI learning at PAS Baitul Qur’an Inclusive Kindergarten reflects inclusive and humanistic educational principles in its planning, implementation, and evaluation. The findings are expected to contribute to the development of adaptive and meaningful Islamic education practices in inclusive early childhood education institutions.